Polymorphism analysis of Valsa mali isolated from Xinjiang Province using ISSR markers. (13th April 2022) - Liu, Hongyan; Wang, Yanxia; Tang, Ling; Hao, Yalun; Deng, Huifang; Zhao, Sifeng; Jin, Chenzhong; Guo, Kaifa
Abstract: Apple quality and quantity is reduced by valsa canker (caused by Valsa mali Miyabe et Yamada) in Xinjiang, China. To develop treatment options, we need to understand its genetic diversity, which was assessed at the molecular level. Eight primers were selected for ISSR‐PCR analysis of 44 strains of apple valsa canker in Xinjiang. The results showed that eight primers amplified a total of 80 clear and reproducible bands including 80 polymorphic loci; the polymorphic loci rate was 100%. Nei's gene diversity index and Shannon's information index were both higher than 0.2 and 0.4 in different geographical regions, which indicated that the genetic diversity of V. mali in Xinjiang was very abundant. The cluster analysis indicated that there was no significant correlation between the genetic relationships and their geographical originals. Core Ideas: The ISSR technology was used to determine the genetic diversity of V. mali in Xinjiang. The results indicated that the genetic variation of V . mali was mainly within the population. We isolated and identified apple and pear canker diseases from throughout Xinjiang. The results show that V. mali in Xinjiang has rich genetic diversity.